Enemies or Allies? Henry George and Francis Amasa Walker One Century Later - Whitaker, John (Journal of Economic Literature, 2016)
An evaluation and commemoration of two pioneering American economists one century after their deaths in 1897. Biographical sketches are followed by expositions and assessments of their contributions to economics. Areas covered include distribution theory, the explanation of poverty, George's single-tax proposal, the business cycle, and money and statistics. A novel interpretation of George's treatment of rent is provided. Also covered are the parallels and antagonisms between George and Walker, and the uneasy relationship between George and the academic economists of the era. An appendix provides a brief guide to the literature.